EGFR blockade in GBM brain tumor stem cells synergizes with JAK2/STAT3 pathway inhibition to abrogate compensatory mechanisms in vitro and in vivo. Issue 1 (18th February 2020) - Jensen, Katharine V; Hao, Xiaoguang; Aman, Ahmed; Luchman, H Artee; Weiss, Samuel
Abstract: Background: The EGFR pathway is frequently mutated in glioblastoma (GBM). However, to date, EGFR therapies have not demonstrated efficacy in clinical trials. Poor brain penetration of conventional inhibitors, lack of patient stratification for EGFR status, and mechanisms of resistance are likely responsible for the failure of EGFR-targeted therapy. We aimed to address these elements in a large panel of molecularly diverse patient-derived GBM brain tumor stem cells (BTSCs). Methods: In vitro growth inhibition and on-target efficacy of afatinib, pacritinib, or a combination were assessed by cell viability, neurosphere formation, cytotoxicity, limiting dilution assays, and western blotting. In vivo efficacy was assessed with mass spectrometry, immunohistochemistry, magnetic resonance imaging, and intracranial xenograft models. Results: We show that afatinib and pacritinib decreased BTSC growth and sphere-forming capacity in vitro. Combinations of the 2 drugs were synergistic and abrogated the activation of STAT3 signaling observed upon EGFR inhibition in vitro and in vivo. We further demonstrate that the brain-penetrant EGFR inhibitor, afatinib, improved survival in EGFRvIII mt orthotopic xenograft models. However, upregulation of the oncogenic STAT3 signaling pathway was observed following afatinib treatment. Combined inhibition with 2 clinically relevant drugs, afatinib and pacritinib, synergistically decreased BTSC viability and abrogated this compensatory mechanism of resistance to EGFR inhibition. A significant decrease in tumor burden in vivo was observed with the combinatorial treatment. Conclusions: These data demonstrate that brain-penetrant combinatorial therapies targeting the EGFR and STAT3 signaling pathways hold therapeutic promise for GBM.